Severe alterations in expression and localisation of α6β4 integrin in salivary gland acini from patients with Sjögren syndrome. Issue 6 (14th July 2008) - Velozo, J; Aguilera, S; Alliende, C; Ewert, P; Molina, C; Pérez, P; Leyton, L; Quest, A; Brito, M; González, S; Leyton, C; Hermoso, M; et al.
Abstract : Objectives: In salivary glands from patients with Sjögren syndrome, overexpression of laminins 1 and 5 and disorganisation of the acinar basal lamina have been reported. Laminin 5 mediates association of the basal lamina with epithelial cells by forming adhesion complexes upon interaction with α6β4 integrin. In the present work, mRNA and protein levels of α6β4 integrin were determined and its localisation in salivary glands evaluated in patients with Sjögren syndrome. Methods: Salivary glands of 12 patients with Sjögren syndrome and 8 controls were studied. The mRNA and protein levels of α6β4 were determined by semiquantitative reverse transcriptase (RT)-PCR and western blot analysis, respectively. The subcellular localisation of α6β4 and laminin were evaluated by confocal microscopy. Results: In patients, no significant differences in α6 and β4 mRNA levels were detected. However, β4 integrin protein levels were significantly lower, whereas, changes in α6, were highly variable. In controls, α6β4 was detected in the basolateral and basal surface of serous and mucous acini, respectively. In patients, alterations in α6β4 distribution were particularly dramatic for acini with strong basal lamina disorganisation. α6β4 was also detected in the cytoplasm and lateral plasma membrane in serous and mucous acini. Conclusion: Mild alterations in the basal lamina correlated with lateral redistribution of α6β4 integrin and the formation of new cell–cell adhesions that help maintain acinar organisation and promote cell survival. Conversely, in cases with severe basal lamina alterations, lateral α6β4 redistribution was no longer sufficient to maintain acinar cell survival. Thus, maintenance of equilibrium between cell–cell and cell–basal lamina attachment is required to sustain gland cell survival.